Sulodexide - unrealized potential in dermatology - Dorota Krasowska; Beata Polkowska-Pruszyńska; Anna Michalak-Stoma (Termedia Publishing House, 2019)
Sulodexide is a highly purified mixture of glycosaminoglycans composed of fast mobility heparin (80%) and dermatan sulfate (20%). Glycosaminoglycans constitute a group of heteropolysaccharides consisting of repeating disaccharide units, which contain amino sugar combined with uronic acid or a hexose. Glycosaminoglycans build glycocalyx covering endothelium of blood vessels, and thus, play an important role in vascular homeostasis. Multi-directional activity of sulodexide including antithrombotic, fibrinolytic, anti-aggregation, anti-inflammatory, anti-proliferative, and anti-oxidative qualities, as well as a high safety profile have allowed using the drug in numerous entities. Advantageous results of sulodexide therapy are observed in diseases involving endothelial damage, prothrombotic or inflammatory states. Thanks to its pleiotropic effects, sulodexide can be also applied in treatment of skin diseases.